THE INFLUENCE OF LIQUIDITY, PROFITABILITY, SOLVENCY AND STOCK PRICES ON STOCK LIQUIDITY LQ 45 - Anita Juwita; Putu Aditya Pratama (Bina Nusantara University, 2022)
This research to determine the effect of liquidity, profitability, solvency and stock prices on stock liquidity of LQ45 for companies listed at the Indonesia Stock Exchange period 2013-2020. The research method uses a quantitative approach and the population were all LQ45 companies listed at the BEI period 2013-2020. The sampling method using non-probability sampling with purposive sampling technique. This study using secondary data of financial statements and analysis technique using panel data regression model Eviews 10. The results showed that liquidity and solvability not affect on stock liquidity of LQ45 companies. Profitability has a positive and significantly effect on stock liquidity of LQ45 companies and stock prices have negative and significantly effect on stock liquidity of LQ45 companies.